EtcABC, a Putative EII Complex, Regulates Type 3 Fimbriae via CRP-cAMP Signaling in Klebsiella pneumoniae - Panjaitan, Novaria Sari Dewi; Horng, Yu-Tze; Cheng, Shih-Wen; Chung, Wen-Ting; Soo, Po-Chi (Frontiers in Microbiology, 2019)
Biofilm formation by Klebsiella pneumoniae on indwelling medical devices increases the risk of infection. Both type 1 and type 3 fimbriae are important factors in biofilm formation by K. pneumoniae. We found that a putative enzyme II (EII) complex of the phosphoenolpyruvate (PEP):carbohydrate phosphotransferase system (PTS), etcA (EIIA)-etcB (EIIB)-etcC (EIIC), regulated biofilm and type 3 fimbriae formation by K. pneumoniae STU1. In this study, the regulatory mechanism of etcABC in K. pneumoniae type 3 fimbriae formation was investigated. We found via quantitative RT-PCR that overexpression of etcABC enhanced the transcription level of the mrk operon, which is involved in type 3 fimbriae synthesis, and reduced the transcription level of the fim operon, which is involved in type 1 fimbriae synthesis. To gain further insight into the role of etcABC in type 3 fimbriae synthesis, we analyzed the region upstream of the mrk operon and found the potential cyclic 3'5'-adenosine monophosphate (cAMP) receptor protein (CRP) binding site. After crp was deleted in K. pneumoniae STU1 and two clinical isolates, these three crp mutant strains could not express MrkA, the major subunit of the ﬁmbrial shaft, indicating that CRP positively regulated type 3 fimbriae synthesis. Moreover, a crp mutant overexpressing etcABC could not express MrkA, indicating that the regulation of type 3 fimbriae by etcABC was dependent on CRP. In addition, deletion of cyaA, which encodes the adenylyl cyclase that synthesizes cAMP, and deletion of crr, which encodes the glucose-specific EIIA, led to a reduction in lac operon regulation and therefore bacterial lactose uptake in K. pneumoniae. Exogenous cAMP but not etcABC overexpression compensated for the role of cyaA in bacterial lactose uptake. However, either etcABC overexpression or exogenous cAMP compensated for the role of crr in bacterial lac operon regulation that would eventually restore lactose uptake. We also found via ELISA and the luxCDABE reporter system that overexpression of etcABC increased intracellular cAMP levels and the transcription level of crp, respectively, in K. pneumoniae. In conclusion, overexpression of etcABC positively regulated cAMP production and cAMP-CRP activity to activate the mrk operon, resulting in increased type 3 fimbriae synthesis in K. pneumoniae.